PREVALENSI KELELAHAN EMPATIK DAN BURNOUT PADA PERAWAT SERTA IMPLIKASINYA BAGI INTERVENSI DUKUNGAN SELAMA PANDEMI COVID-19 - Inero V. Ancho; Castillo-Merca, Michelle; Gil Z. Albor, Rufo; Joel B. Botor, Nephtaly; S. Bulasag, Abriel; Perez Almeda, Phrygian (Journal of Health Service Management, 2025)
Background: The COVID-19 pandemic placed unprecedented stress on healthcare workers, particularly nurses, who served as frontline responders in high-stress environments. Objectives: This study examines the prevalence of compassion fatigue (CF) and burnout among nurses at a Philippine tertiary hospital during the pandemic and explores their associations with demographic factors and professional variables. Methods: A descriptive cross-sectional design was employed, utilizing the Professional Quality of Life Scale (ProQOL) to measure CF, burnout, and compassion satisfaction. The study surveyed 27 nurses, with results indicating moderate levels of CF, burnout, and compassion satisfaction. Results: A strong positive correlation (r = 0.858, p < 0.05) was found between CF and burnout, confirming their interconnected nature, while the relationship between CF and compassion satisfaction was weak and not statistically significant. No significant correlations were found between CF and demographic factors such as age, gender, marital status, or years of practice, suggesting that CF is primarily influenced by occupational stress rather than personal characteristics. Conclusions: These findings underscore the urgent need for institutional interventions, such as resilience training, mental health support, and structured peer support systems, to mitigate CF and burnout among nurses. Addressing these concerns is essential to sustaining nurses' well-being and ensuring the continued provision of high-quality patient care